오탁방지막이 설치된 3차원 흐름 수치모델 - 홍남식(NAMSEEG HONG); 김가야(GAYA KIM); 강윤구(YOON-KOO KANG) (Han-guk haeyang gonghak hoeji (Online), 2008)
In this study, a mathematical model for flaw with silt protector is proposed that adds a second-order energy loss term in the momentum equation. The three-dimensional numerical model was developed based on mathematical models and verified through comparison with flume test results. Loss coefficients were evaluated through the flume tests and applied to the numerical model. It was found through the investigation of various example cases that the downstream flow pattern was affected mainly by penetration of the silt curtain, not by the approach velocity, and also that the blocking effect of velocity was increased by the increase in mesh density of the silt curtain, below a certain mesh density. The blocking effect did not increase further above a certain mesh density.